Does using testicular sperm retrieval rather than ejaculated spermatozoa improve reproductive outcomes in couples with previous ART failure and poor ovarian response? A case‐controlled study. (1st December 2017) - Gilman, A.R.; Younes, G.; Tannus, S.; Son, W.Y.; Chan, P.; Buckett, W.
Summary: The objective of this study was to assess whether testicular‐retrieved spermatozoa improve reproductive outcomes compared to fresh ejaculate in women with poor ovarian response and a history of previous ART failure. The study was performed as a retrospective case–control study at a university‐based reproductive center in Montreal, Quebec, Canada. Eighteen poor‐responder patients were matched 3 : 1 with 54 controls. Poor responders were defined as those with ≤3 oocytes retrieved at oocyte pickup. Cases were identified as poor responders, and only those with previous IVF failure(s) as an indication for testicular‐retrieved spermatozoa were included. Controls were age and cycle attempt number matched. All patients were included only once. From January 1, 2009 to December 31, 2015, all patients and controls underwent an IVF cycle using ICSI with either testicular spermatozoa or ejaculated spermatozoa, respectively. Outcomes included live birth rate, pregnancy rate, miscarriage rate, oocyte number, and embryo transfer (ET) day. The results showed live birth rates, pregnancy rates, and miscarriage rates were similar. There were fewer day 2 ETs (8.5% vs. 48.6%, p = 0.01) and more day 5 blastocyst transfers (25.0% vs. 5.4%, p = 0.05) in the testicular sperm retrieval group compared to controls and thus an overall suggestion of better embryo quality in the testicular sperm group. Overall, however, the use of testicular sperm retrieval appears to add little. Women with poor ovarian response typically have a poor prognosis with respect to live birth rates, and this is further supported in this study. The suggestion of better embryo quality in the testicular‐retrieved sperm group would need to be further assessed in a larger multicentered study.